Treatment of upper limb lymphedema with low-level laser: a systematic review - Silvia Elizate Monteiro; Lilian Valim Resende; Mônica Faria Felicíssimo; Angélica Rodrigues de Araújo; Camila Teixeira Vaz
Introduction Low-level lasers have been suggested as a complement to lymphedema treatment. However, this therapy's mechanism of action and its effects are poorly understood up to the present. Objective To conduct a systematic literature review to analyze the effects of low-level laser in the treatment of upper-limb lymphedema in women submitted to breast cancer surgery. Material and methods Randomized clinical trials were included, in Portuguese, English and Spanish, from January 1990 to July 2013. The article search was carried out in the Pubmed, Lilacs and PEDro electronic databases, with the following descriptors:Terapia a Laser de Baixa Intensidade, Linfedema, Câncer de Mama, Low-level laser therapy, Lymphedema, Breast Neoplasms and also through a manual search. Results and discussion Low-level lasers have been used for treating several acute and chronic conditions. However, its application for managing post breast cancer surgery is still recent, often based on empirical evidence. Treating upper-limb lymphedema with low-level laser presented positive results, with reduction in the circumference or volume of the affected limb. Conclusion More studies of high methodological quality are needed in order to better understand the mechanism of action of low-level laser on the lymphatic system and its effects on lymphedema treatement.